Extraction and characterization of Jatropha curcas L. as natural coagulant and its application for turbidity removal - Khodapanah, Nasrin (2014)
Coagulation is a critical step in water production process not only because it removes colloidal particles but it also gets rid of microorganisms that are often attached to the particles. The use of aluminium sulphate and other synthetic chemicals as commonly-used coagulants, has caused some environmental and health problems. Additionally, the cost of the imported chemicals and the disposal of scheduled sludge in hard currency have made to consider the natural coagulants as a promising alternative. In the present study, the potentials of natural coagulants extracted from various parts of plants and animal tissue which are indigenous and abundantly available in Southeast Asia were investigated. The most promising natural coagulant from the preliminary screening study was the seeds from Jatropha curcas. In terms of feasibility study, Jatropha seed is potential candidate as coagulant due to its availability in Malaysia and the low price of raw material. Additionally, Jatropha press cake is a byproduct of biodiesel production which so far has not had any widely special application in Malaysia. Dragon fruit foliage was removed from potential natural coagulant list due to lack of access; currently there is no available supplier in Malaysia and Southeast Asia that can supply the dragon fruit foliages for water treatment purpose. Moringa seed copes with the problems of availability, sustainability and high price in Malaysia; there is no available plantation in Malaysia for Moringa seeds. A main problem of application of chitosan for turbidity removal was smelling an unpleasant fishy odor of treated water by chitosan. In addition, water treatment plants are confronted by operation problems due to water solubility and overdosing complications of using chitosan. After removal of oil from J. curcas kernel, several experiments were conducted on press cake to identify the parameters with significant effects on the turbidity reduction. To minimize the turbidity at pH 5 and 6 of synthetic turbid water by improvement of the extraction condition, the experiments were carried out using jar tests and a full factorial central composite design and response surface methodology (RSM) were applied to model the active agent extraction. The optimum condition for extraction of the active ingredient from J. curcas press cake was by using 13 mM NaOH and 0.1 M NaCl at an extraction temperature of 52C and an extraction time of 5 min to achieve a minimum turbidity at pH 5 and 6 of turbid water. Chemical analysis of two-coagulant solutions, distilled water extract (DWE-JcPc) and optimum condition extract (OCE-JcPc) of J. curcas press cake, showed the protein recoveries at 7.49±0.62% and 61.55±2.34% from the total solid dissolved, respectively. The active component isolation stage was then carried out using isoelectric precipitation followed by the dialysis. The active ingredient of J. curcas -extract coagulant was a protein with molecular weight 30-35 kDa. In a synthetic turbid water using kaolin particles at pH 5, OCE-JcPc coagulant reduced turbidity by at least 90% for a wide range of initial turbidities. It was discovered that the coagulant performance was sensitive to the initial pH of the water. The zeta potential of OCE-JcPc was found to be negative at its original pH, confirming that the negative charges are predominant in the crude coagulant solution. On the other hand, Ca2+ ions improved kaolin coagulation by OCE-JcPc. The coagulation mechanism of OCE-JcPc was postulated to be an enmeshment of kaolin with the net-like structure. In the case of Ca2+ ion (bivalent cations), at least 0.2 mM was necessary for coagulation at 10 mg/L dose of OCE-JcPc. The treatment of river water by OCE-JcPc in comparison with aluminum sulphate (Alum) showed that OCE-JcPc in the presence of bivalent cations performed better than alum in turbidity reduction. Water with final turbidity of less than 5 NTU, total solids 5 mg/L and chemical oxygen demand 43.75 mg/L was achieved when 80 mg/L of OCE-JcPc natural coagulant and 2.5 mM of CaCl2 were used to treat the river water at initial pH level of 6.87. In another study, OCE-JcPc also reduced the turbidity of acidic river water by 4.6 NTU with total solids at 6.7 mg/L and chemical oxygen demand at 137 mg/L when 260 mg/L of OCE-JcPc natural coagulant and 0.5 mM of CaCl2 were used. Additionally, the combination of 192 mg/L alum + 30 mg/l OCE-JcPc gave the lowest residual turbidity for the acidic river water sample corresponds to 40% savings in alum usage. This study concluded that natural coagulant solution extracted from J. curcas press cake has good coagulation properties for a wide range of conditions and would be a promising alternative coagulant to alum.